Ekstraksi Kalsium dari Cangkang Kerang Hijau (Perna viridis L.) dan Kerang Batik (Paphia undulata B.) dengan Metode Kalsinasi sebagai Sediaan Effervescent - Usman, Mohammad Rofik; Nabila, Rifka; Hakiki, Lutfiah Nurul (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
One of the solutions is the supplying of calcium effervescent powder as a source of calcium. The source of calcium that has not been processed maximally is the clam shell. Calcium from the clam shells will be extracted by calcination method at 900 °C for 4 hours. The extracted clam shells powder are tested using XRD and analyzed using the Rietveld method. The particle sizes of calcium are determined by the Scherer equation. The best calcium is formulated into 3 formulations with several variations in composition. Evaluation of calcium effervescent powder includes organoleptic test, water content and dispersion time. The extracted calcium crystal diffractogram shows the CaO compound with cubic structure and space group FM3M. The particle sizes of CaO nanoparticles from green shells and batik were 88.7597nm and 96.66566nm, respectively. The best CaO based on χ2 values ​​and particle sizes are CaO from green clamshells. The organoleptic test of the three formulations produced the same data as yellow, granular shape, and citrus aroma. Formulation three is the best formulation based on the low water content and short dispersion time.